PROSPECTS OF BUILDING A PROSPEROUS SOCIETY IN THE NEW UZBEKISTAN THROUGH AN ANTI-POVERTY STRATEGY (Scientific journal of the Fergana State University, 2023)
This article describes the socio-philosophical analysis of the prospects and directions of building a prosperous society in the new Uzbekistan through the strategy of fighting against poverty. Also, in the article, the essence and directions of the social protection policy implemented in our country in the following years, the reform plans presented in the programmatic foundations of the fight against poverty are revealed and analyzed.